2019
DOI: 10.1021/acsanm.8b02146
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Scintillating Ce3+-Doped Lu2Si2O7 Nanoparticles Using the Salt-Supported High Temperature (SSHT) Method: Solid State Chemistry at the Nanoscale

Abstract: The synthesis of lutetium silicate nanoparticles doped with Ce 3+ using the new salt-supported high temperature (SSHT) method is reported. This mechanochemical−thermal method enables the synthesis of nanoparticles without aggregation even after long calcination times of 48 h at high temperatures. These nanoparticles are characterized by powder X-ray diffraction (PXRD), transmission electron microscopy (TEM), energy dispersive spectroscopy (EDS), and Fourier transform infrared spectroscopy (FT-IR). Their optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Following the first report of scintillation response in quantum dots (QDs) by Létant and Wang in 2006 [ 33 ], several other emerging materials platforms, low-dimensional platforms, have been proposed and evaluated including metal halide perovskites [ 34 ], [ 35 ], all inorganic perovskites [ 36 ], organic–inorganic layered perovskites, scintillating nanotubes [ 37 ], [ 38 ], lanthanide-doped nanoparticles [ 7 ], [ 10 ], and metal–organic frameworks [ 39 ], [ 40 ]. In addition to rare-earth doped nanoscintillators, various types of oxides [ 41 ], [ 42 ], halides [ 43 ], sulfides [ 44 ], and oxysulfides scintillating nanostructures [ 45 ] with varying refractive index have been designed and evaluated offering a tunable range of scintillation wavelength, morphology, decay lifetime, and radiation hardness. Despite a plethora of advantages including outstanding spectral range tunability and flexibility of design, nanoscintillators can suffer from low quantum yield originating from thermal quenching and large self-absorption compared to their bulk counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Following the first report of scintillation response in quantum dots (QDs) by Létant and Wang in 2006 [ 33 ], several other emerging materials platforms, low-dimensional platforms, have been proposed and evaluated including metal halide perovskites [ 34 ], [ 35 ], all inorganic perovskites [ 36 ], organic–inorganic layered perovskites, scintillating nanotubes [ 37 ], [ 38 ], lanthanide-doped nanoparticles [ 7 ], [ 10 ], and metal–organic frameworks [ 39 ], [ 40 ]. In addition to rare-earth doped nanoscintillators, various types of oxides [ 41 ], [ 42 ], halides [ 43 ], sulfides [ 44 ], and oxysulfides scintillating nanostructures [ 45 ] with varying refractive index have been designed and evaluated offering a tunable range of scintillation wavelength, morphology, decay lifetime, and radiation hardness. Despite a plethora of advantages including outstanding spectral range tunability and flexibility of design, nanoscintillators can suffer from low quantum yield originating from thermal quenching and large self-absorption compared to their bulk counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…As a key part of detectors, scintillators have been extensively used in high-energy radiation detection and medical imaging. It can absorb radiation and convert the energy into light, which can be further converted into electronic signals to obtain digital images. The scintillators play a decisive role in the resolution of the image.…”
Section: Introductionmentioning
confidence: 99%
“…19 The growing mechanism of Y 2 SiO 5 nanocrystals has been confirmed by Zhou et al 20 They found that the hollow Y 2 SiO 5 nanoparticles could be obtained by phase transition of the YOHCO 3 @SiO 2 core−shell structure and mutual diffusion of the Y 2 O 3 core and SiO 2 shell and that the Kirkendall effect plays a crucial role in the annealing process. 21 Egodawatte et al prepared Ce 3+ -doped Lu 2 Si 2 O 7 nanoparticles using a new saltsupported high-temperature method with long calcination times of 48 h. 22 However, the drawback of these methods is the high calcinate temperature or the long calcination time required for the preparation process, and these processes may lead to large, aggregated, irregular particles which result in not being suitable for biomedical application.…”
Section: Introductionmentioning
confidence: 99%